Fibrinogen levels in relation to colorectal cancer onset: A nested case-cohort study from the Moli-sani cohort - Parisi, Roberta; Panzera, Teresa; Russo, Laura; Gamba, Sara; De Curtis, Amalia; Di Castelnuovo, Augusto; Marchetti, Marina; Cerletti, Chiara; Falanga, Anna; de Gaetano, Giovanni; Donati, Maria Benedetta; Iacoviello, Licia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with cancer are commonly characterized by abnormalities in laboratory coagulation tests, underlying a subclinical hypercoagulable condition. Due to the involvement of the hemostatic system in cancer patients, some of its biomarkers, such as fibrinogen, could be a useful tool in predicting cancer risk. We performed a case-cohort study to evaluate the relationship among fibrinogen levels and colorectal cancer (CRC). Methods In the framework of Moli-sani Study (N = 24,325, enrolled 2005–2010) a subcohort of 1,290 individuals (55.0% women; mean age 55.0 ± 12.0 years) was selected and compared with 126 CRC cases identified during a follow-up of 4.3 years. Incident cases of colorectal cancer were ascertained by direct linkage with hospital discharge forms according to the International Classification of Disease (ICD-9-CM) codes: 153–154. Events were validated through medical records and confirmed by histological reports. Fibrinogen levels were measured in frozen citrated plasma samples. Hazard Ratio (HR) and 95% confidence interval (CI), adjusted by relevant covariates were estimated by a Cox regression model using Prentice method. Results Individuals with levels of fibrinogen ≥400 mg/dL had a higher hazard to develop colorectal cancer when compared to those with lower levels after adjustment for sex and age (HR: 1.81; 95% CI 1.12–2.92). Additional adjustment for CRC family history, income, physical activity, diabetes medication and hypercholesterolemia did not modify the result (HR: 1.91; 95% CI 1.15–3.17). Analyses stratified by age and sex showed a most evident association in elderly (HR: 2.30; 95% CI: 1.10–4.81) and in women (HR: 2.28; 95% CI: 1.08–4.81). Sensitivity analyses confirmed the main findings, showing independence from a potential role of confounding by a large panel of biomarkers, including inflammation and hemostasis factors. Conclusion Our results, based on a case-cohort study from a general adult population apparently free from any cancer during the recruitment, showed that fibrinogen levels ≥400 mg/dL were positively and independently associated with CRC, suggesting that this glycoprotein could be a potential biomarker for this type of cancer and supporting the “common soil hypothesis” in the pathophysiology of cardiovascular disease and tumors.